EYE PATHOLOGIES IN FACIOSCAPULOHUMERAL MUSCULAR DYSTROPHY (CASE REPORT AND LITERARY ANALYSIS) - E. V. Denisova; L. A. Katargina; L. V. Kogoleva; M. V. Belova; N. A. Osipova; E. V. Fedoseeva (Российский офтальмологический журнал)
In addition to the classic Coats’ disease characterized by retinal vascular telangiectasias and aneurysmal dilatations surrounded by yellowish intra- and subretinal exudates and developing in somatically healthy children, Coats’-like retinal changes can occur in a number of systemic diseases and complicate the course of other eye pathologies. One of the diseases that occur with Coats’-like exudative vasculopathy is facioscapulohumeral muscular dystrophy, or Landouzy - Dejerine disease. Systemic manifestations of this pathology are the myodystrophic process, which usually affects muscles of the face and arms and distal muscles of the legs, as well as sensorineural hearing loss, respiratory failure, cardiac arrhythmia, in the infantile form - mental retardation and episyndrome. The paper describes two clinical cases involving children with facioscapulohumeral muscular dystrophy, presents the results of treatment, and discusses the importance of a systematic approach in examining patients with Coats’-like retinal changes. For citation: Denisova E.V., Katargina L.A., Kogoleva L.V., Belova M.V., Osipova N.A., Fedoseeva E.V. Eye pathologies in facioscapulohumeral muscular dystrophy (case report and literary analysis). Russian ophthalmological journal. 2018; 11 (3): 50-4 (In Russian). doi: 10.21516/2072-0076-2018-11-3-50-54